Pyrotinib Combined With Vinorelbine in HER2-Positive Metastatic Breast Cancer: A Multicenter Retrospective Study - Li, Yi; Qiu, Yixuan; Li, Huihui; Luo, Ting; Li, Wei; Wang, Hong; Shao, Bin; Wang, Biyun; Ge, Rui (Frontiers in Oncology, 2021)
Introduction: Pyrotinib plus capecitabine has been approved in China for human epidermal growth factor receptor 2 (HER2)-positive metastatic breast cancer (MBC). Meanwhile, vinorelbine is another important chemotherapy option for MBC available in oral and intravenous forms. Thus, pyrotinib plus vinorelbine may represent a new treatment option, particularly for patients with failed capecitabine treatment. This study reported the first real-world data for pyrotinib plus vinorelbine therapy in HER2+ MBC. Methods: HER2+ MBC patients (n = 97) treated with pyrotinib plus vinorelbine in six institutions across China from May 2018 to June 2020 were enrolled. Progression-free survival (PFS), objective response rate (ORR), overall survival (OS), and toxicity profiles were determined. Results: Sixty-seven percent of patients received more than two lines of systematic therapy. Nearly all patients (97.9%) had received trastuzumab and 50.5% were administered lapatinib. When combined with pyrotinib, 74.2% received oral and 25.8% received intravenous vinorelbine. Median PFS (mPFS) was 7.8 (range, 4.7–10.8) months for all patients. The mPFS in patients administered pyrotinib as second-line therapy and third-or-higher-line therapy were 12.0 and 6.4 months, respectively. Patients who received pyrotinib plus oral or intravenous vinorelbine had similar mPFS (7.8 vs. 6.4 months, p = 0.871). The 23 patients with brain metastases had mPFS of 6.3 (range, 3.4–9.2) months. Lapatinib-naïve patients had significantly longer PFS than lapatinib-treated patients (10.8 months vs. 5.6 months, p = 0.020). Median OS was not achieved. The ORR for 96 patients was 34.3%. Common grade 3 and 4 adverse events were diarrhea (22.7%), neutropenia (7.2%), and leukopenia (4.1%). Conclusions: Pyrotinib plus vinorelbine therapy demonstrated promising effects in HER2+ MBC with tolerable toxicity, particularly in patients with second-line treatment and without prior lapatinib treatment, as well as in patients with brain metastases. Oral vinorelbine is a useful alternative to the intravenous form when combined with pyrotinib. Clinical Trial Registration: ClinicalTrials.gov, Identifier: NCT04517305.